Odpowiedź:
zad. 1
[tex]7a + (2b + 3) = 7a + 2b + 3 \\ 8x - (y + 9) = 8x - y - 9 \\ - (3m - 3) + n = - 3m + 3 + n = - 3m + n + 3[/tex]
zad. 2
[tex] - 5a + 2b - (2a - 3b) = - 5a + 2b - 2a + 3b = - 3a + 5b \\ (4x - 7y) + (3x + 7) = 4x - 7y + 3x + 7 = 7x - 7y + 7 \\ ( - x + b) - (3x - 2b) + 3x = - x + b - 3x + 2b + 3x = - x + 3b[/tex]
zad. 3
[tex]2x(3x - 1) + 4x = 6 {x}^{2} - 2x + 4x = 6 {x}^{2} + 2x \\ 3a(4a + 5b) - 2(3a + 2b) = 12 {a}^{2} + 15ab - 6a - 4b \\y(x + 4) + 2x( {x}^{2} - 5y) = xy + 4y + 2 {x}^{2} - 10xy = 2 {x}^{2} - 9xy + 4y[/tex]